Efficient and Stable Perovskite White Light‐Emitting Diodes for Backlit Display. (13th February 2023) - Chen, Shuxin; Lin, Jidong; Zheng, Song; Zheng, Yuanhui; Chen, Daqin
Abstract: High‐quality backlit display puts forward urgent demand for color‐converting materials. Recently, metal halide perovskites (MHPs) with full spectral tunability, high photoluminescence quantum yields (PLQYs), and high color purity have found potential application in wide‐color‐gamut display. Regrettably, naked MHPs suffer from long‐term instable issue and cannot pass harsh stability tests. Herein, amorphous‐glass‐protected green/red CsPbX3 quantum dots (QDs) are prepared by elaborately optimizing glass structure, perovskite concentration, and in situ crystallization. PLQYs of green CsPbBr3 @glass and red CsPbBr1.5 I1.5 @glass reach 94% and 78%, respectively, which are the highest ones of CsPbX3 @glass composites reported so far and comparable to colloidal counterparts. Benefited from complete isolation of QDs from external environment by glass network, CsPbX3 @glass can endure harsh commercial standard aging tests of 85 °C/85%RH and blue‐light‐irradiation, which are applied to construct white light‐emitting diodes (wLEDs) with high external quantum efficiency of 13.8% and ultra‐high luminance of 500 000 cd m −2 . Accordingly, the perovskite wLED arrays‐based backlit unit and a prototype display device are designed for the first time, showing more vivid and wide‐color‐gamut feature benefited from narrowband emissions of CsPbX3 QDs. This work highlights practical application of CsPbX3 @glass composite as an efficient and stable light color converter in backlit display. Abstract : High‐quality display puts forward urgent demand for color‐converting materials. Herein, amorphous‐glass‐protected green/red CsPbX3 quantum dots with high emissive yields of 94%/78% and super stability are applied to construct white light‐emitting diodes (wLEDs). A prototype display device based on perovskite wLEDs arrays backlight shows more natural and real color restoration for its wide color gamut feature.